KAJIAN ANTROPOLOGI SASTRA CERITA RAKYAT DATUMUSENG DAN MAIPA DEAPATI (Anthropology of Literature Analysis Datu Museng dan Maipa Deapati Folklore) - Salmah Djirong (Balai Bahasa Sulawesi Selatan, 2014)
Anthropology of literature is one of literary analysis that discusses the relationship between literature and culture focused on how the literature is used in daily life as guide of conduct in society. Anthropology of literature is to describe the structure of literature (novel, short story, poetry, drama, folklore) and to relate the concept or social cultural context. Method used in the research is directed to enthnographic aspects or cultural society, society’s mindset, inheritage cultural tradition from time to time and still done. Data obtained is analyzed and explained descriptively. The aim and result intended to gain are descriptions of anthropology aspect, whether religion, myth, law, or tradition found in Datu museng dan Maipa Deapati.